Effects of aerobic exercise with blood flow restriction on cardiorespiratory and functional capacity in the elderly: a systematic review (Acta Scientiarum. Health Sciences, 2024)
This study systematically reviewed the available scientific evidence regarding the chronic changes promoted by aerobic exercise (AE) combined with blood flow restriction (BFR) on cardiorespiratory capacity (CC) and functional capacity (FC) in the elderly. Search in PubMed, Web of ScienceTM, Scopus, and Google Scholar databases was carried out considering the period from January 1990 to November 2020. To this end, the following descriptors were used in English: ((blood flow restriction training) OR (blood flow restriction exercise) OR (vascular occlusion training) OR (vascular occlusion exercise) OR (kaatsu training)). Out of the 3,091 articles identified, 3,073 were excluded based on title and abstract, accounting for 99.41% of the total. Thus, 18 articles were obtained and read in full. Of the 18 articles, 16 were excluded as they did not meet the criteria for methodological quality analysis. Two articles were selected for critical consideration. Both studies found that AE combined with BFR improved CC and FC after six weeks of training. Aerobic training performed with RFS for six weeks improves FC and suggests an improvement in CC in the elderly.